The influence of an applied standard test method on a measurement of concrete stabilized secant modulus of elasticity - Domagała, Lucyna; Dobrowolska, Justyna (MATEC web of conferences, 2018)
The paper focuses on the influence of the standard test method applied to determine the concrete stabilized secant modulus on a specified value. The new European Standard EN 12390-13 for testing hardened concrete accepts two methods (A and B) for the determination of the secant modulus of elasticity in compression. The aim of the research was to establish how different testing procedures affect a measured value of modulus of elasticity. Four structural concrete series: two lightweight aggregate concretes and two normal-weight ones were subject to tests of moduli of elasticity determined by both standard methods, as well as compressive strength and density. The carried out tests revealed that the procedure of testing modulus of elasticity influenced a measured value. Method A led to higher values of modulus in relation to Method B, irrespective of concrete density and strength. Nevertheless, a certain relationship between the concrete structure homogeneity and the difference in results of moduli determined by both methods may be observed.